Meritocratic and fair? The discourse of UK and Australia's widening participation policies. Issue 7 (21st January 2021) - Coyle, Maeve; Sandover, Sally; Poobalan, Amudha; Bullen, Jonathan; Cleland, Jennifer
Abstract: Introduction: Globally, people with the academic and personal attributes to successfully study medicine experience disadvantages associated with sociodemographic factors. Governments have attempted to address this issue via macrolevel policies aimed at widening participation (WP) to medicine. These policies differ by country, suggesting much can be learned from examining and comparing international policy discourses of WP. Our question was: How are discourses of WP to higher and medical education positioned in the UK and Australia? Methods: A systematic search strategy was guided by five a priori themes inspired by United Nations Sustainability Goals (2015). Seventeen policy documents (UK n = 9, Australia n = 8) published between 2008 and 2018 were identified. Analysis involved two over‐arching, iterative stages: a document analysis then a Foucauldian critical discourse analysis, the latter with the aim of unveiling the power dynamics at play within policy‐related discourses. Results: Discourses of social mobility and individual responsibility within a meritocracy are still paramount in the UK. In contrast, the dominant discourse in Australia is social accountability in achieving equity and workforce diversity, prioritising affirmative action and community values. Similarities between the two countries in terms of WP policy and policy levers have changed over time, linked to the divergence of internal drivers for societal change. Both nations recognise tensions inherent in striving to achieve both local and global goals, but Australia appears to prioritise community values in working towards 'nation building' whereas in the UK the focus on individuality and meritocracy at times seems at odds with achieving parity for disadvantaged individuals. Discussion: WP policies and practices are situated and contextual so caution must be taken when extrapolating lessons from one context to another. The history of a country and the nature of marginalisation in that country must be scrutinised when trying to understand what drives WP policy. Abstract : While the UK and Australia recognise tensions between local and global goals, Australia appears to prioritise community values and 'nation building' whereas UK discourses focus on social mobility and individual responsibility.